The Banach-Saks Properties in Orlicz-Lorentz Spaces - Anna Kamińska; Han Ju Lee (Abstract and Applied Analysis)
The Banach-Saks index of an Orlicz-Lorentz space Λφ,w(I) for both function and sequence case, is computed with respect to its Matuszewska-Orlicz indices of φ. It is also shown that an Orlicz-Lorentz function space has weak Banach-Saks (resp., Banach-Saks) property if and only if it is separable (resp., reflexive).